Searching for Balance between Hill Country Pastoral Farming and Nature - John R. Dymond; Adam J. Daigneault; Olivia R. Burge; Chris C. Tanner; Fiona E. Carswell; Suzie Greenhalgh; Anne-Gaelle E. Ausseil; Norman W. H. Mason; Beverley R. Clarkson (Land, 2023)
Much land has been cleared of indigenous forest for pastoral agriculture worldwide. In New Zealand, the clearance of indigenous forest on hill country has resulted in high food production, but waterways have become turbid, with high nutrient and E. coli concentrations. A range of on-farm mitigations are available, but it is unclear how they should be applied catchment-wide. We have developed a catchment-scale model that integrates economics with ecosystem services to find a better balance between agriculture and nature. In the upper Wairua catchment, Northland, if three actions are prioritised—(1) keeping stock out of streams, (2) constructing flood retention bunds in first-order catchments, and (3) planting trees on highly erodible land—then sediment loads, E. coli levels, and flooding are significantly reduced. Implementing these actions would cost approximately 10% of catchment net revenue, so it is feasible with a combination of regulation and subsidy. Many catchments in New Zealand are primarily pastoral agriculture, as in other countries (in North and South America, Australasia, and the United Kingdom), and would benefit from the analysis presented here to guide development along sustainable pathways. While pastoral agriculture typically stresses waterways, with increased sedimentation and freshwater contaminants, much can be done to mitigate these effects with improved farm and riparian management.